(untitled) (Research, Society and Development, 2021)
With the advance of the pandemic of the pathogen Coronavirus SARS-CoV-2, which causes the disease Covid-19 (Coronavirus Disease), being considered today a great threat on a global scale, a diet rich in functional properties in the combat and prevention of diseases is recommended. symptoms of this pathology. Thus, the research aims to present the importance of the functional properties of babassu coconut in immunological support and in combating the inflammatory syndrome caused by Covid-19. This is a descriptive bibliographic review with a qualitative approach to the scientific literature, covering the period from 2010 to January 2021. As a result, the nutritional supply with functional properties improves the immune function and helps to cope with inflammation, reducing the severity of diseases inflammatory. Thus, controlling inflammation is an effective strategy to reduce the severity of Covid-19, and babaçu coconut mesocarp flour is a supplementation option to combat inflammatory processes precisely because it is a natural antioxidant and anti-inflammatory food. . It is concluded that the Babaçu coconut mesocarp flour constitutes a highly nutritious food supplement and with a great capacity to treat various pathologies, its probable potential for treating the symptoms of Covid-19, including the Respiratory Syndrome, is justified Acute Grave, because its composition is formed by several vitamins and minerals, making it a deeply anti-inflammatory and antioxidant food.